From cybernetjcstothe imagery of digital communications - Salas, Octavio (2008)
Cybernerits, proposed by Norbert Wiener which admits ro be considered as the seven basic, hisrorical sources of communicarion rhinking, represents an obliged starting point in every study done, from the possible medi a analysis, with the purpose of exploring the imagery of rhe "Informarion and Knowledge Sociery". The study of information technologies has been considered by many Latín American scholars and researchers as a mauer of minor conceptual hierarchy in communications studies. Media ecology represents one of the schools in rhe possible med ia analysis, which has rigurously studied the new information technologies. Media ecology has a basis rhe thesis of Marshall McLuhan, and after the last years it has been enriched with the contribution of recognized thinkers, who have mosdy passed u nnoticed in Latín America. T he wonderful development of digital communicarions forces us to underrake an exhausted and rigorous critical revision of the possible media analysis, which would surely allow the identification of a consideable accumulation of "obsolete knowledge" (Toffler). Advertising investment in new d igital media regisrers constant increment every year, while decreases rhe investment destined ro convencional mass media. The development of digital media - fo rero Id by Wiener-, sooner or later will produce structural changes in the study plans and programs for degrees or post-graduare degrees in Mass Commun ications. If ir is noticed rhe importance which admits the hi ring of our graduares, changes must be immediate.